REFORMULASI KONSEP PLEA BARGAINING SEBAGAI PEMBARUAN HUKUM ACARA PIDANA INDONESIA BERBASIS KEADILAN BERMARTABAT - syifa alam; Dominikus Rato; Bayu Dwi Anggono (Law Department, University of Widya Gama Mahakam Samarinda, 2024)
Abstract Background: Some of the problems in the criminal process in court include the accumulation of settlement of criminal cases and the bureaucracy of a long trial The Plea Bargaining concept that has been implemented in the United States can be adopted in Indonesia while considering the values of Pancasila based on integrative theory (integratif theory) and the theory of dignified justice (keadilan bermartabat theory). Research Metodes: The research method used is normative juridical. This research uses a conceptual approach, a statutory approach, a comparative approach and a historical approach. Findings: The results of this research involve the reformulation and explanation of the ontological, epistemological, and axiological aspects of the concept of plea bargaining. There are provisions in the Draft Criminal Procedure Law that do not yet reflect the concept of plea bargaining. Reformulation of the concept of plea bargaining is based on the theory of dignified justice (keadilan bermartabat theory), so that the creation of the purpose of the law of dignified justice that is rooted in the values and the national spirit or the soul of the nation (volksgeist). Conclusion: By adopting the concept of plea bargaining that has been formulated based on dignified justice, it can solve the problem of stacking criminal case settlement in courts and trial bureaucracy and as a form of Criminal Procedure Law Reform in Indonesia. Keywords: reformulation; Plea Bargaining concept, theory of dignified justice; Pancasila. Abstrak Latar Belakang: Sebagian permasalahan dalam persidangan pidana di pengadilan antara lain penumpukan penyelesaian perkara pidana dan birokrasi persidangan yang cukup lama. Konsep Plea Bargaining yang telah diterapkan di negara Amerika dapat di adopsi di negara Indonesia dengan tetap mempertimbangkan nilai-nilai Pancasila berdasarkan teori integratif dan teori keadilan bermartabat. Metode Penelitian: Metode penelitin yang digunakan adalah yuridis normatif. Penelitian ini menggunakan metode pendekatan konseptual (conceptual approach), pendekatan perundang-undangan (statute approach), pendekatan perbandingan (comparative approach) dan pendekatan historis (historical approach). Hasil Penelitian: Hasil penelitian ini adalah mereformulasi dan menjelaskan aspek ontologi, epistimologi dan aksiologi konsep plea bargaining. terdapat pasal di Rancangan Hukum Acara Pidana yang belum mencerminkan konsep plea bargaining, reformulasi Konsep plea bargaining yang berbasis teori keadilan bermartabat dapat diejawantahkan dalam Rancangan Hukum Acara Pidana. Reformulasi konsep plea bargaining ini berdasarkan teori keadilan bermartabat, sehingga terciptanya tujuan hukum yaitu keadilan bermartabat yang berakar pada nilai-nilai dan semangat nasional atau jiwa bangsa (volksgeist). Kesimpulan: Dengan mengadopsi konsep plea bargaining yang telah direformulasi berbasis keadilan bermartabat dapat menyelesaikan permasalahan penumpukan penyelesaian perkara pidana di Pengadilan dan birokrasi persidangan serta sebagai bentuk pembaruan hukum acara pidana di Indonesia. Kata kunci: Reformulasi; konsep plea bargaining; teori keadilan bermartabat; Pancasila.